Revisional Breast Surgery: Are Surgical Plans Changed if the Patient Has a Textured Device?. (May 2021) - Nava, Maurizio; De Vita, Roy; Catanuto, Giuseppe; Tunesi, Gianfranco; Rocco, Nicola
Abstract : Summary: The authors reviewed the available evidence on revision surgery following implant-based breast surgery with the aim of investigating whether any difference in the surgical approach should be proposed if the patient has a textured device. They included in their review 31 studies presenting different approaches for revision surgery following implant-based breast surgery (both aesthetic and reconstructive), with a level of evidence ranging from 4 to 5. None of the included studies proposed different surgical approaches for revision surgery in patients carrying textured devices. The authors conclude that no different surgical attitudes in revision surgery following implant-based breast surgery should be adopted if the patient has a textured device according to the available evidence, when a correct approach is performed to face the complication or adverse event, following a thorough preoperative study of the patient with the proper diagnostic tools.